Children's voices, family disputes and child-inclusive mediation : the right to be heard - Barlow, Anne; Ewing, Jan (Bristol University Press, 2024)
EPDF and ePUB available Open Access under CC-BY-NC-ND licence. Considered from a children's rights perspective, this book provides a critical socio-legal account of child-inclusive mediation (CIM) practice. It draws on interviews with relationship professionals, mediators, parents and children to consider the risks and benefits of CIM.
Keywords: Family mediation.; Family counseling.; Children's rights.; Médiation familiale.; Familles -- Counseling.; Enfants -- Droits.; LAW / Family Law / Divorce & Separation.; Electronic books.